Interacciones reacción-transporte en sedimentos mixtos siliclástico-carbonatados de la Ría de Vigo y bahía de Baiona. - Gago-duport, L.; García, T.; Santos, A.; Velo, A.; Vilas, Federico; Fernández-bastero, S. (Journal of Iberian Geology, 2000)
The general sedimentation trends, leading a particular space-distribution in mixed siliciclastic-carbonated environments are usually explained as resulting from the interplay between several dynamical processes, affecting to both, the siliciclastic and the carbonated fractions and given rise to an average spatial distribution mainly determined by the grain size. Nevertheless, together the dynamical factors, the mixing of siliciclastic and carbonated sediments involves a great variety of sedimentological, biological and chemical processes that are understimated when the depositional models take into account exclusivately mechanical variables as the forcing parameters determining a particular grain-size distribution. In order to assess the existence of different mixing processes, for every mineral involved on both, the siliciclastic and carbonate constituents, a comparative study between the general sedimentary pattern and the single mineral behaviour is needed. This procedure may help to evidence control mechanisms opperating between processes and products in this kind of mixing environments. Therefore, the time evolution of the general sedimentary pattern can be considered as the result of a multi-source system, where the signature of local controls are shown by deviations on the average trends. Consequently, in this work we have evaluated the chemical control factors that can interplay with the hydrodinamical ones to give self-organised configuration of sedimentary patterns during the mixing between the siliciclastic and carbonatic fractions. In particular, these mechanisms are related to the dissolution-precipitation processes taking place between minerals through the seawater and following specific rate laws for every mineral and grain-size.